충남 서산 지역 2020년 겨울철 측정 방법에 따른 Brown Carbon (BrC)의 광흡수 계수 특성 비교 - 이혜연(Hye Yeon Lee); 옥수민(Sumin Ok); 김나은(Naeun Kim); 이광열(Kwangyul Lee); 정민혜(MinHye Jung); 신혜정(Hye-Jung Shin); 양재환(Jae-Hwan Yang); 정진상(Jinsang Jung) (한국대기환경학회지(국문), 2023)
In order to compare light absorption characteristics of atmospheric brown carbon (BrC) according to analytical methods, PM2.5 samples were collected at the Chungcheong Air Environment Research Center located in Seosan-si, Chungcheongnam-do during winter 2020. After aqueous extraction of the PM2.5 samples, the light absorption coefficient of BrC (babs,BrC) was analyzed using a liquid waveguide capillary cell (LWCC) coupled with a UV/Vis spectrometer. babs,BrC was also retrieved from 7-λ light absorption coefficients measured by an AE33 aethalometer. During the entire measurement period, average organic carbon (OC) and elemental carbon (EC) concentrations were measured to be 4.5±3.9 μgC/m3 and 1.5±1.2 μgC/m3, respectively, whereas water-soluble OC (WSOC) concentration was 1.4±0.55 μgC/m3. Average babs,BrC at 370 nm measured by the LWCC-UV/Vis spectrometer and aethalometer were 1.40±0.6 Mm-1 and 17.0±9.4 Mm-1, respectively. Mass absorption efficiency (MAE) of BrC at 370 nm obtained by the LWCC-UV/Vis spectrometer and aethalometer were determined to be 1.0±0.2 m2 g-1 and 11.6±3.2 m2 g-1, respectively. It was found that babs,BrC and MAE obtained by the aethalometer were much higher than those by the LWCC-UV/Vis spectrometer, indicating that light absorption characteristics of BrC is highly influenced by analytical methods. KCI Citation Count: 0